Vor 50 Jahren: Erste erfolgreiche Behandlung einer akuten Herztransplantat-Abstoßungskrise - Land, Walter G. (DMW - Deutsche Medizinische Wochenschrift, 2018)
The first clinical use of the “Munich antilymphocyte globulin” (ALG) at the occasion of the first successful human heart transplantation is briefly described. The cardiac transplantation was carried out by Christiaan Barnard and his team in Cape Town, South Africa, in 1968. The patient developed an acute allograft rejection which could be successfully reversed within three weeks using the intravenous administration of ALG. This event can be regarded as the beginning of a success story of ALG in its use as a powerful immunosuppressive agent in all categories of clinical organ transplantation.
Keywords: Münchener Antilymphozytenglobulin; erste erfolgreiche Herztransplantation